(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2024)
Religious moderation education needs to be taught to children from an early age in order to form good character and prevent the development of ideologies that can damage social stability. This study examines the role of religious moderation in early childhood character building through the perspective of Tafsir Al-Azhar by Buya Hamka. The method used is the literature study method with a descriptive-analytic approach. The data sources in this study consist of primary sources, namely Tafsir Al-Azhar by Buya Hamka and secondary sources derived from previous studies on moderation and early childhood education. The results show that the application of religious moderation in early childhood education can form characters that are inclusive, tolerant, fair, and balanced in religious and social life. This moderation education not only helps children to be fair and wise, but also serves as a filtering medium against the impact of extremist ideologies that threaten community harmony.